Optimization Design for Determination of Polycyclic Aromatic Hydrocarbons in Water Samples - Chen, W.; Sun, A.D.; Xu, Q.C. (Asian Journal of Chemistry, 2012)
A response surface optimized method was proposed for the analysis of polycyclic aromatic hydrocarbons in drinking water using dispersive liquid phase microextraction and gas chromatography mass spectrometry. Methanol was selected as the dispersive solvent and perchloroethylene as the extraction solvent. The volume of the extraction solvent, the volume of dispersive solvent and the solution pH were all important parameters. Their reproducibility was investigated under the optimized conditions. The relative standard deviations ranged from 9.0-11.3 %. The limits of detection, based on a signal-to-noise ratio of three, ranged from 0.52-1.67 ng/L, lower than that established by the Environmental Protection Agency.